ANALISIS PENGARUH KEPUTUSAN PEMBELIAN ONLINE DI LAZADA (STUDI KASUS PADA LINGKUNGAN MAHASISWA UPN VETERAN JAKARTA) - Christiono Hartawan, (2020)
This research uses quantitative descriptive method which is carried out on online purchasing decisions at Lazada. Lazada is one of the largest market places in Indonesia which was founded in 2012 and launched in Indonesia in 2014. The purpose of this study is to find out and prove whether purchasing decisions at Lazada are influenced by trust, service quality, and price. The population in this study were active students of UPN Veteran Jakarta who had shopped at Lazada. Samples taken as many as 75 respondents with purposive sampling method. By distributing questionnaires to students who have shopped at Lazada. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is PLS (Partial Least Square). The results showed that the trust variable had no effect and was not significant to the purchase decision with a path coefficient of 0.156. While the quality of service has an influence and significant effect on purchasing decisions with a path coefficient of 0.485. price and significant influence on purchasing decisions with a path coefficient of 0.320. Adjusted R-Square purchase decision is 0.763 which means the contribution of trust, service quality, and price to the purchase decision is 0.763 and the remaining 0.237 is influenced by other variables.